Atmospheric drought in Belgium – statistical analysis of precipitation deficit. (28th October 2015) - Zamani, Sepideh; Gobin, Anne; Van de Vyver, Hans; Gerlo, Jeroen
ABSTRACT: The principle of return periods or frequencies of natural hazards is adopted in many countries as the basis of eligibility for the compensation of associated losses. For adequate risk management and eligibility in Belgium, hazard maps for drought events with a 20‐year return period are needed. The maximum precipitation deficit in the summer half‐year (1 April–30 September) was taken as a good indicator for atmospheric drought severity during a particular year. Precipitation deficit is calculated as a cumulative balance between precipitation and evapotranspiration for a free open water surface, short grass, deciduous forest and coniferous forest. Precipitation deficit maxima were modelled with the generalized extreme value (GEV) distribution. Mapping precipitation deficit return levels is based on a GEV distribution where the parameters vary smoothly in space as a function of altitude and distance to the sea. The final products are return level maps of extreme precipitation deficit, relevant for insurance companies providing cover for the forestry and agriculture sector.